Koperasi dalam Perspektif Ekonomi Syari’ah - Nur S. Buchori (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2010)
This article explains about cooperative economic system in the perspective of Islamic Law (Shari’ah). Cooperative Islamic Economics system is inspired by Islamic values. Cooperative economic system in the perspective of Islamic values is different from the other economic system like capitalism and socialism. The Islamic values opposes to exploitation by the owners of capital against workers who are poor, and prohibit the accumulation of wealth. The aims cooperative economic system in Islamic system are to create welfare all of members, distribution of proverty, brotherhood, and social goodness (maslahah al-amm). In the cooperative of sharia, very transaction (tasharruf) based on the use of effective whether for financing or everyday needs. Both of these are treated differently. For productive activities, such as members get a tender from the other party can then use the results to the contract principle of musharaka or mudaraba while transportation equipment or other tools can use the principle of buying and selling with murabahah, greetings or istishna. Runway Cooperative Association of Islamic Sharia as other economic institutions namely referring to the Islamic economic system itself, as implied by the phenomenon of the universe and is also written in the Qur’an and al-Hadith.